Determinasi Upaya Pemulihan Kerugian Keuangan Negara Melalui Peran Kejaksaan terhadap Perampasan Aset Tindak Pidana Korupsi - Fajri Kurniawan; Muhammad Syammakh Daffa Alghazali; Afdhal Fadhila (CV Rewang Rencang, 2022)
Loss of state finances is a form of corruption that has been stipulated in the legislation. The form of the return of the loss is carried out by the mechanism of asset confiscation. However, this is not explicitly regulated in the Criminal Code, Law no. 31 of 1999 jo. UU no. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, Law no. 17 of 2003 concerning State Finance as well as in Law no. 1 of 2004 concerning the State Treasury. The presence of the Prosecutor's Asset Recovery Center (PPA) as an asset recovery center plays a role in carrying out asset recovery activities, providing assistance, as well as coordinating and ensuring that every stage of asset recovery can be integrated by realizing good governance.